Swimsuits used by elite male swimmers in the 13th FINA world Championship: analysis of freestyle events - Neiva, Henrique P. (2010)
Several world records have been broken in recent years. Swimming community speculates this fact is partly related due to the changes in swimsuits characteristics. To swim faster one need to increase the thrust and reduce drag, which can be achieved wearing the new polyurethane swimsuits (Marinho et al., 2009). The purpose of this study was to verify the distribution of different swimsuits used by male swimmers during all the freestyle finals, according to the different distances swum, at the last world championships being held at Rome in 2009.